Adaptive MIMO-OFDM combining space-time block codes and spatial multiplexing in correlated frequency-selective channels - Halmi, Mohd Hairi (2005)
This thesis propose a novel adaptive multiple-input multiple-output (MIMO) orthogonal frequency division multiplexing (OFDM) system combining space-time block codes (STBC) and spatial multiplexing (SM). It is a dynamic, robust and high data rate wireless transmission system. The strength of the proposed system lies in its ability to utilise the time, frequency and space dimensions of signal transmission through the use of adaptive loading technique, OFDM scheme and MIMO technology.